1999
DOI: 10.1002/1529-0131(199906)42:6<1093::aid-anr5>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1?, interleukin-1 receptor antagonist, interleukin-4, and interleukin-10 gene polymorphisms: Relationship to occurrence and severity of rheumatoid arthritis

Abstract: This report, for the first time, indicates an association between RA and a polymorphic IL-4 gene sequence located in 5q31-33. In addition, the results show the prognostic value of a polymorphism in IL-1beta exon 5, which allowed prediction of erosive disease with a specificity of 91.8% in 42.1% of patients. Although these observations are very interesting, they have to be considered preliminary and will need to be confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
149
2
7

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(171 citation statements)
references
References 31 publications
10
149
2
7
Order By: Relevance
“…11 The IL-10G12 allele we have observed at a higher frequency is found predominantly (especially in RA patients) with the ACC haplotype, and less frequently with GCC. In contrast with GCC, the ACC haplotype is reported to be a low IL-10 in vitro producer when lymphocytes are stimulated by concanavalin-A.…”
Section: Genetic Polymorphisms In Spanish Ra Patients a Martinez Et Almentioning
confidence: 74%
See 1 more Smart Citation
“…11 The IL-10G12 allele we have observed at a higher frequency is found predominantly (especially in RA patients) with the ACC haplotype, and less frequently with GCC. In contrast with GCC, the ACC haplotype is reported to be a low IL-10 in vitro producer when lymphocytes are stimulated by concanavalin-A.…”
Section: Genetic Polymorphisms In Spanish Ra Patients a Martinez Et Almentioning
confidence: 74%
“…10 Some studies of IL-10 polymorphisms in RA have also been reported, mostly with negative results. [11][12][13] IL-1Ra (interleukin-1 receptor antagonist) is a member of the IL-1 family, which also includes IL-1a and IL-1b. IL-1Ra binds to the IL-1 receptor but fails to transmit a signal to the target cell, thereby behaving as a natural antagonist of IL-1.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that IL-1␤ plays a role in several inflammatory diseases, such as in the severity of RA and in inflammatory bowel disease (1)(2)(3). In addition, the IL1 gene cluster has been identified as a significant region of linkage to OA of the hand (20), and more recently, Meulenbelt et al (25) demonstrated a significant genetic association between the T allele at Ϫ511 of the IL1B gene and allele 2 in the IL-1RN variable-number tandem repeat and OA of the hip.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine interleukin-1 (IL-1) is a primary mediator in the pathogenesis of diseases such as rheumatoid arthritis (RA), osteoarthritis (OA), asthma, and inflammatory bowel disease (1)(2)(3). The activity of IL-1 is derived from 2 distinct polypeptides, IL-1␣ and IL-1␤, whose production and activity are regulated by transcriptional and posttranslational mechanisms, as well as from a natural antagonist, IL-1 receptor antagonist (IL-1Ra).…”
mentioning
confidence: 99%
“…In a study done on RA patients, the authors found a weak association of two polymorphisms in the IL-4 gene, the IL-4 −590C/T*T allele and IL-4 intron 3 VNTR repeat 1 {which has been shown to be in tight linkage disequilibrium with +33 C/T SNP in an earlier study (Suppiah et al, 2005)} with susceptibility to the disease (Maksymowych et al, 2002). Existing data from in vitro and in vivo studies (Rosenwasser and Borish, 1997;Kawashima et al, 1998;Cantagrel et al, 1999) suggest that the −590 C/T*T allele which is in tight linkage disequilibrium with the +33 C/T*T allele is associated with increased IL-4 expression. In this present study, there is a significant underrepresentation of the +33 C/T*TT homozygotes in the female patients.…”
Section: Discussionmentioning
confidence: 99%